Dental stem cells and their applications in pediatric dentistry - Aldomyati, Roaa M.; Alghamdi, Hussain K.; Alzahrani, Eman I.; Alkhudhayr, Lama M.; Binthabit, Sultanah M.; Subahi, Jumana H.; Alzahrani, Fawaz H.; Alsulaimani, Mawaddah N.; Algarni, Shihnaz M.; Abdulaziz, Mariam G.; Almusayyab, Othoob T. (International Journal Of Community Medicine And Public Health, 2023)
Regenerative medicine has garnered significant attention due to its transformative impact on disease management and the restoration of optimal bodily functions. Stem cells, a cornerstone of regenerative medicine, are particularly renowned for their remarkable capacity to facilitate tissue regeneration and repair, revolutionizing modern healthcare by offering diverse treatment avenues for multiple conditions. Dental pulp stem cells (DPSCs), a subset of postnatal stem cells, are especially noteworthy for their extensive proliferation and ability to differentiate into various specialized cell types. In the realm of pediatric dentistry, there exists a pressing need for advancements in regenerative medicine. Thorough research in this domain has the potential to propel evidence-based pediatric dentistry, ensuring that children receive tailored, high-quality care. Stem cells hold immense promise in pediatric dentistry by offering less invasive and regenerative solutions for a range of childhood dental issues and congenital anomalies. This research, initiated on 04 October 2023, was instigated following an exhaustive review of existing literature utilizing databases like PubMed, Web of Science, and Cochrane. The literature search encompassed a wide array of medical terminologies. Dental stem cells are categorized into four major types: DPSCs, stem cells from human exfoliated deciduous teeth (SHED), stem cells of the apical papilla (SCAP), and periodontal ligament stem cells (PDLSCs). Pediatric dentistry, encompassing endodontics, orthodontics, periodontics, and the treatment of craniofacial defects, stands to benefit significantly from the potential of dental stem cells. The preservation of dental pulp stem cells extracted from deciduous and permanent teeth through tooth banking offers a source for future regenerative therapies. The preservation process involves multiple comprehensive steps. In summary, dental stem cells present a promising avenue within pediatric dentistry, offering multifaceted applications ranging from pulpal regeneration and dentin repair to orthodontic support and the treatment of craniofacial anomalies.